2017
DOI: 10.18203/2320-6012.ijrms20175442
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of FNAC in diagnosis of lymphadenopathy-a retrospective study from a regional cancer centre, Cuttack, Odisha

Abstract: Background: Lymphadenopathy is one of the most common clinical presentations and major causes of morbidity. Thus, clinical recognition and urgent diagnosis is of paramount importance. So, we aimed to analysis the diagnostic role of fine needle aspiration cytology (FNAC) in superficial lymphadenopathy in a regional cancer centre, Odisha, India.Methods: A total 1129 cases were retrieved from the hospital record retrospectively from the patients who had presented with superficial lymphadenopathy from January 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Study conducted by Malhotra et al (2017) 12 was on total 238 cases but only 113 were followed by histopathological examination and hence only those findings were compared and included in the discussion. Same with study by Pathy (2017) 13 with total cases being 1129 but only 399 followed up for histopathology. The present study showed close similarity with other studies in case of sensitivity (93.33%) and PPV (93.33%).…”
Section: Lymph Node: (Tablesmentioning
confidence: 76%
“…Study conducted by Malhotra et al (2017) 12 was on total 238 cases but only 113 were followed by histopathological examination and hence only those findings were compared and included in the discussion. Same with study by Pathy (2017) 13 with total cases being 1129 but only 399 followed up for histopathology. The present study showed close similarity with other studies in case of sensitivity (93.33%) and PPV (93.33%).…”
Section: Lymph Node: (Tablesmentioning
confidence: 76%
“…FNAC is a procedure used to procure fluid, cells and tissues by means of a disposable syringe with a thin needle inserted for diagnosing masses. 3 Greig and Gray in 1904 used it first to diagnose trypanosomiasis. In 1921 Guthrie used fine-needle aspiration on lymph nodes for diagnosis on lymph node sand was further used as a diagnostic tool in 1930 by Martin and Ellis.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the spectrum of lymphadenopathy in a particular area is important for making a definitive diagnosis [1]. Various researchers have described the pattern of diseases diagnosed on the basis of FNAC of peripheral lymph nodes in different parts of the country [6][7][8][9][10][11][12][13].Very few studies regarding this have been done in this area. Hence, this study was conducted.…”
Section: Introductionmentioning
confidence: 99%